L'ethnicité comme ressource politique: partage de l'espace urbain et gestion de la diversité à Montréal et Bordeaux - Poirier, Cécile (Institut national de la recherche scientifique et Université du Québec à Montréal, 2005)
Keywords: Bordeaux; Parc-Extension (quartier); Quartiers; Saint-Michel; YMCA

L’ethnicisation de l’établissement humain en Amérique du Nord: l’exemple du quartier portugais à Montréal - Lavigne, Gilles; Daudelin, Nanouk; Ritchot, Gilles (Cahiers de géographie du Québec, 1995)
Keywords: Portugais; Quartiers

La division de l'espace résidentiel montréalais en fonction de la langue maternelle: apport des indices de ségrégation - Apparicio, Philippe; Séguin, Anne-Marie (Canadian Journal of Urban Research / Revue canadienne de recherche urbaine, 2002)
Keywords: Francophones

La communauté roumaine de Montréal une géographie ethnique - Vasilescu, Miruna (Université du Québec à Montréal, 2000)
Keywords: Roumains

Fin ou renaissance des quartiers? Les significations des territoires de proximité dans une ville pluriethnique - Dansereau, Francine; Germain, Annick (Espaces et Sociétés, 2002)
Keywords: Quartiers

L’insertion résidentielle des jeunes issus de l’immigration à Montréal - Séguin, Anne-Marie; Rose, Damaris; Mongeau, Jaël (Publication IM, 2003)
Keywords: Logement

La mise en place des paysages ethniques, 1871-1971 - McNicoll, Claire (Montréal 2001. Visages et défis d'une métropole, 1998)

Espaces ethniques en devenir: une enquête géographique sur les Haïtiens et les Vietnamiens de Montréal - Guillemette-Roc, Diane (Université du Québec à Montréal, 1986)
Keywords: Haïtiens; Vietnamiens

À propos du patrimoine urbain des communautés culturelles: nouveaux regards sur l'espace public - Germain, Annick; Contin, Mabel; Liégeois, Laurence; Radice, Martha (Les temps de l'espace public urbain: construction, transformation et utilisation, 2008)
Keywords: Patrimoine

La communauté libanaise à Montréal: essai de géographie culturelle - Lami, Nathalie (Université du Québec à Montréal, 1992)
Keywords: Libanais

La fluidité de l'espace montréalais: étude sur la diffusion de la diversité ethnoculturelle à Montréal entre 2001 et 2006 - Leloup, Xavier (The Canadien Geographer / Le Géographe canadien, 2015)

La présence haïtienne à Montréal: évolution démographique et spatiale - Bastien, André (Cahiers québécois de démographie, 1986)
Keywords: Haïtiens

Montréal, une ville multiethnique, entre appropriations et représentations - Germain, Annick (S'approprier la ville: le devenir-ensemble, du patrimoine urbain aux paysages culturels, 2015)
Keywords: Quartiers

Le boulevard Saint-Laurent et son histoire-(suite 2) - Tessier, Stéphane (Il était un fois... Montréal Nord, 2023)
Keywords: Chinois; Juifs; Saint-Laurent (rue)

Ethnicité et paysage. Le marquage ethnique dans un Montréal aux identités plurielles - Paré, Sylvie (La ville autrement, 2005)
Keywords: Quartiers

Montreal-Glasgow - Marshall, Bill (University of Glasgow French and German Publications, 2005)
Keywords: Écossais

Building a Neighbourhood in Montreal - Lavigne, Gilles; Teixeira, Carlos (The Portuguese in Canada: From the Sea to the City, 2000)
Keywords: Portugais; Quartiers

Montréal en Amérique du Nord - Mercer, John (Montréal: tableaux d'un espace en transformation, 1992)

Immigrants et forums internet: les représentations de la géographie résidentielle des russophones à Montréal - Richard, Myriam (Institut national de la recherche scientifique et Université du Québec à Montréal, 2011)
Keywords: Internet; Logement; Russes

Pratiques vernaculaires et design urbain: le cas de la communauté portugaise de Montréal - Hajjar, Béatrice (Université de Montréal, 2000)
Keywords: Portugais

Residential Patterns of New Immigrants and Linguistic Integration - Montgomery, Catherine; Renaud, Jean (The Canadian Geographer / Le Géographe canadien, 1994)
Keywords: Langue; Quartiers

Residential Segregation of Visible Minorities in Canada's Gateway Cities - Bauder, Harald; Sharpe, Bob (The Canadian Geographer / Le Géographe canadien, 2002)
Keywords: Logement

Les espaces multiples de la fête: la Saint-Jean-Baptiste 1968 à nos jours - Gérin, Annie (British Journal of Canadian Studies, 2014)
Keywords: Nationalisme; Saint-Jean-Baptiste (fête)

Citystats and the History of Community and Segregation in Post-Second World War Urban Canada - Stanger-Ross, Jordan (Journal of Canadian Historical Association / Revue de la Société historique du Canada, 2008)
Keywords: Autochtones; Juifs

La représentation symbolique dans le contexte de la mondialisation. L'exemple de la construction identitaire du Quartier chinois de Montréal - Cha, Jonathan (Journal of the Society for the Study of Architecture in Canada/Journal de la société pour l’étude de l’architecture au Canada, 2004)
Keywords: Chinois; Quartier chinois; Quartiers

Le temple tamoul Śri Murugan de Dollard-des-Ormeaux (Montréal) : Mobilisation d'une communauté, construction physique et transmission d'une tradition ancestrale - Boisvert, Mathieu (Journal of the Society for the Study of Architecture in Canada/Journal de la société pour l'étude de l'architecture au Canada, 2012)
Keywords: Patrimoine; Sri Lankais

Leonardo da Montreal: The Rhetoric of Italianità and the Canadian Post-Nation - Fratiloiu, Raluca Maria (Université Concordia, 2006)
Keywords: Centre Leonardo Da Vinci; Italiens

Owing Allegiance: The British Community in Verdun, Québec during the Second World War - Durflinger, Serge Marc (Canadian Ethnic Studies / Études ethniques au Canada, 2004)
Keywords: Britanniques; Guerre; Quartiers; Verdun

Espaces observés: ethnicité et appropriation territoriale - Le Gall, Josiane; Meintel, Deirdre (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

L’aménagement des lieux de culte des minorités ethniques: enjeux et dynamiques locales - Germain, Annick; Gagnon, Julie Elizabeth; Polo, Anne-Lise (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2003)

'Britain Today' at Expo 67 - Darling, Elizabeth (Expo 67: Not Just a Souvenir, 2010)
Keywords: Britanniques; Expositions

Genèse d'une communauté lesbienne: un récit des années 1970 - Hildebran, Andrea (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)
Keywords: Anglophones; Femmes; Francophones

Motivation in Hip-Hop Graffiti Culture: The Site of Tension between Individual Desire, Peer Influence and Community Space - Rahn, Janice (Université Concordia, 1999)

Les premiers Italiens de Montréal: l'origine de la Petite Italie du Québec - Ramirez, Bruno (Boréal Express, 1984)
Keywords: Italiens; Petite-Italie (quartier); Quartiers

Les églises et les bâtiments à caractère religieux de Montréal : de la francisation à la patrimonialisation - Bernier, Lyne (Université de Bretagne Occidentale, 2015)
Keywords: Conservation; Patrimoine; Églises

Des sociétés distinctes. Gouverner les banlieues bourgeoises de Montréal, 1880-1939 - Bérubé, Harold (Studies on the History of Quebec / Études d'histoire du Québec, 2015)
Keywords: Banlieue; Mont-Royal (quartier); Pointe-Claire; Quartiers; Westmount

Le boulevard Saint-Laurent dans la Petite-Italie: 1930, 1960 - Trépanier, Mathieu Alexandre (Université du Québec à Montréal, 2014)
Keywords: Italiens; Petite-Italie (quartier); Quartiers; Rues; Saint-Laurent (rue)

Saint-Michel et la Cité des arts du cirque. Un partenariat en évolution - Trudelle, Catherine; Klein, Juan-Luis (Montréal : la cité des cités, 2017)
Keywords: Carrière Miron; Cirque; Quartiers; Saint-Michel

The Changing Landscape of Religious Diversity in Montreal - Castel, Frédéric; Dejean, Frédéric; Germain, Annick (Engaging with Diversity. Multidisciplinary Reflections on Plurality in Quebec, 2018)
Keywords: Musulmans; Protestants; Églises

Sacred ground on de la Savane: Montreal's Baron de Hirsch Cemetery - Kucharsky, Danny (Véhicule Press, 2008)
Keywords: Cimetières; Juifs

A Gift for Their Mother: The Saidye Bronfman Centre Theatre. A History - Gold, Muriel (Productions Miri, 2007)
Keywords: Juifs; Théâtre

Bienvenue dans la Petite-Italie de Montréal - Taschereau, Sylvie (Cap-aux-Diamants, 2019)
Keywords: Italiens; Petite-Italie (quartier); Quartiers

“The Most Distinctively Canadian City” Representations of the City in Montreal Guidebooks, 1876–1892 - Lamoureux, François (Urban History Review/Revue d'histoire urbaine, 2023)
Keywords: Anglophones; Métropole; Tourisme

“The People Who Stayed”: Back River Memorial Gardens Cemetery as a Site of Jewish Migrant and Montreal Urban Meaning-Making - Frost, Naomi; Sheftel, Anna (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Ahuntsic; Cimetières; Juifs

La paroisse Holy Family: une empreinte de la présence anglophone dans l'arrondissement - Vailles, Alexis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Anglophones; Rosemont; Églises

Transforming the Ideal: Visions and Revisions of Housing in a French-Canadian Community, 1942-1995 - Gilliland, Jason A. (Université McGill, 1996)
Keywords: Cité-Jardin du tricentenaire; Logement

Les descendants d'Hochelaga: étude de la représentation autochtone à travers le toponyme Hochelaga et les productions artistiques et commerciales du Vieux-Montréal - Doiron, Roger (Université du Québec à Montréal, 1998)
Keywords: Autochtones; Quartiers; Vieux-Montréal

L'histoire des quartiers d'immigration à Montréal: vers la construction d’une mémoire au-delà des territoires? - Germain, Annick (Migrance, 2009)
Keywords: Quartiers

L'accès au logement par les nouveaux arrivants à Montréal: le cas des réfugiés et demandeurs d'asile en provenance d'Afrique subsaharienne - Charette, Alexandra (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2010)
Keywords: Africains; Logement

Le municipal à l’épreuve de la multiethnicité: aménagement des lieux de culte dits ethniques et crise du zonage à Montréal - Germain, Annick (Les règles du jeu urbain, entre droit et confiance, 2006)

The Segregated City: Class Residential Patterns and the Development of Industrial Districts in Montreal 1861 and 1901 - Lewis, Robert D. (Journal of Urban History, 1991)
Keywords: Locataires; Logement; Mobilité résidentielle

Les écrits urbains sous contrôle. L'exemple de Montréal - Artières, Philippe (Essais, 2014)
Keywords: Enseignes; Français; Publicité

Public Space as Nation: Construction National Culture After Independence - N. Cook, Danielle (California State University, 2014)
Keywords: Francophones; Nationalisme

Les territoires fluides de l’immigration à Montréal ou le quartier dans tous ses états - Germain, Annick; Poirier, Cécile (Globe: revue internationale d’études québécoises, 2007)
Keywords: Quartiers

The harp and the shamrock: the two faces of Montreal's Irish community - Bâby, Françoise (The Westmount Historian, 2023)
Keywords: Griffintown; Irlandais

Jackie Robinson...Un Américain à Villeray - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2024)
Keywords: Baseball; Noirs; Villeray

Religion et culture, pour moi c'est pareil. Le temple hindou tamoul montréalais, une institution culturelle - Boisvert, Mathieu (Le Québec APRÈS Bouchard-Taylor: les identités religieuses de l'immigration, 2012)
Keywords: Sri Lankais

Le «boom» des immeubles d’appartements à Montréal de 1921-1951 - Choko, Marc H. (Urban History Review / Revue d'histoire urbaine, 1994)
Keywords: Logement; Outremont; Westmount

Le boulevard Saint-Laurent et son histoire-(suite 1) - Tessier, Stéphane (Il était un fois... Montréal Nord, 2023)
Keywords: Juifs; Saint-Laurent (rue)

Everyday Cosmopolitan Place Making: Multiethnic Commercial Streets in Montreal Neighbourhoods - Radice, Martha (Institut national de la recherche scientifique et Université du Québec à Montréal, 2010)
Keywords: Rues

La commande publique dans un contexte de diversité ethnoculturelle: débat entourant l'érection du monument La réparation (1994-1998) - Alvarez Hernandez, Analays (Université du Québec à Montréal, 2010)
Keywords: Arméniens; Monuments; Turcs

Entre les rues Coloniale et Saint-Urbain. Les Juifs ashkénazes dans les années 1930 - Olazabal, J.-Ignace (Bulletin d'histoire politique, 2001)
Keywords: Juifs

Cultural Diversity in Mile End: Everyday Interactions between Hasidim and Non-Hasidim - Alton, Caitlin J. (Université Concordia, 2011)
Keywords: Juifs; Mile End; Quartiers

Ethnicity and Home Ownership in Montreal, 1921–51 - Choko, Marc H. (Urban History Review / Revue d'histoire urbaine, 1998)
Keywords: Locataires; Logement

Les banlieues de l'immigration ou quand les immigrants refont les banlieues - Germain, Annick; Rose, Damaris; Richard, Myriam (Histoire de Montréal et de sa région, 2012)
Keywords: Banlieue; Italiens; Mile End; Mobilité résidentielle; Parc-Extension (quartier); Petite-Italie (quartier); Quartiers; Saint-Léonard

Building and Reshaping the Suburban Landscape: The Role of Immigrant Communities - Germain, Annick; Rose, Damaris; Richard, Myriam (Montreal: The History of A North American City, 2018)
Keywords: Banlieue; Italiens; Mile End; Mobilité résidentielle; Parc-Extension (quartier); Petite-Italie (quartier); Quartiers; Saint-Léonard

Le monument inattendu, le Monument-National, 1893-1993 - Larrue, Jean-Marc (Cahiers du Québec - Collection Histoire, 1993)
Keywords: Société Saint-Jean-Baptiste; Théâtre; École nationale de théâtre du Canada

Qui a eu cette idée folle un jour d'inventer l'école? (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2013)
Keywords: Juifs; Plateau Mont-Royal; Quartiers

Loisirs dansants de la bourgeoisie anglo-montréalaise. Transformation et persistance des lieux de pratique, 1870–1940 - Roquigny, Peggy (Urban History Review / Revue d'histoire urbaine, 2011)
Keywords: Anglophones; Bourgeoisie; Danse

Patrimoine religieux (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2018)
Keywords: Académie Marie-Rose; Arts sacrés; Carmélites; Communautés religieuses; Conservation; Juifs; Patrimoine; Plateau Mont-Royal; Protestants; Quartiers; Sculpture; Églises

Entre rupture et transmission: les pratiques alimentaires italiennes autour du marché Jean-Talon - Masson-Labonté, Amélie; Gagnon, Marie-Anne (Cap-aux-Diamants, 2019)
Keywords: Alimentation; Italiens; Jardins; Marchés

Synagogue Architecture in Canada: A Summary History - Stiefel, Barry L. (Journal of the Society for the Study of Architecture in Canada, 2021)
Keywords: Juifs

« Glad of your help »: Scottish Architects in Montreal, 1860-1940 - Adams, Annmarie (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Golden Square Mile; Royal Victoria Hospital; Écossais

Église St. Patrick - Noppen, Luc (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Irlandais; Patrimoine; Saint-Patrick (église)

Au temps de la fondation de Montréal, Pointe-à-Callière - Poussart, Annick (Pointe-à-Callière, Cité d'archéologie et d'histoire de Montréal, 2017)
Keywords: Archéologie; Autochtones; Callière, Louis-Hector de; Chomedey de Maisonneuve, Paul de (Maisonneuve, Paul de Chomedey de); Mance, Jeanne; Musée Pointe-à-Callière; Musées; Pointe-à-Callière

When Montréal was founded, Pointe-à-Callière - Poussart, Annick (Pointe-à-Callière, Cité d'archéologie et d'histoire de Montréal, 2017)
Keywords: Archéologie; Autochtones; Callière, Louis-Hector de; Chomedey de Maisonneuve, Paul de (Maisonneuve, Paul de Chomedey de); Mance, Jeanne; Musée Pointe-à-Callière; Musées; Pointe-à-Callière

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Routes; Saint-Laurent (rue)

John George Savage. Un habitant notable de Dorval/John George Savage. A notable Dorval resident - Nieuwendyk, Dick (Héritage Dorval, 2023)
Keywords: Anglicans; Dorval; Peinture

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde